Acute myocardial infarction in a patient with dextrocardia and successful angioplasty - Bishnu H. Subedi (Greater Baltimore Medical Center, 2017)
A 48-year-old man with dextrocardia presented with atypical chest pain for 2 hours. Right-side ECG showed convex upward ST elevations in leads V4 and V5. Coronary angiogram showed complete occlusion of mid portion of the left anterior descending artery (LAD). Several attempts at engaging the left main origin was successful and the LAD was opened with placement of a drug-eluting stent. The post-procedure course was uneventful, and he was discharged home two days later.